A novel survivin dimerization inhibitor without a labile hydrazone linker induces spontaneous apoptosis and synergizes with docetaxel in prostate cancer cells. (1st July 2022) - Peery, Robert; Cui, Qingbin; Kyei-Baffour, Kwaku; Josephraj, Sophia; Huang, Caoqinglong; Dong, Zizheng; Dai, Mingji; Zhang, Jian-Ting; Liu, Jing-Yuan
Graphical abstract: Abstract: Survivin, a member of the inhibitor of apoptosis protein family, exists as a homodimer and is aberrantly upregulated in a wide spectrum of cancers. It was thought to be an ideal target due to its lack of expression in most adult normal tissues and importance in cancer cell survival. However, it has been challenging to target survivin due to its "undruggable" nature. We previously attempted to target its dimerization domain with a hypothesis that inhibiting survivin dimerization would promote its degradation in proteasome, which led to identification of a lead small-molecule inhibitor, LQZ-7F. LQZ-7F consists of a flat tetracyclic aromatic core with labile hydrazone linking a 1, 2, 5-oxadiazole moiety. In this study, we tested the hypothesis that LQZ-7F could be developed as a prodrug because the labile hydrazone linker could be hydrolyzed, releasing the tetracyclic aromatic core. To this end, we synthesized the tetracyclic aromatic core (LQZ-7F1) using reported procedure and tested LQZ-7F1 for its biological activities. Here we show that LQZ-7F1 has a significantly improved potency with submicromolar IC50's and induces spontaneous apoptosis in prostate cancer cells. It also more effectively inhibits survivin dimerization and induces survivin degradation in a proteasome-dependent manner than LQZ-7F. We also show that the combination of LQZ-7F1 and docetaxel have strong synergism in inhibiting prostate cancer cell survival. Together, we conclude that the hydrazone linker with the oxadiazole tail is dispensable for survivin inhibition and the survivin dimerization inhibitor, LQZ-7F, may be developed as a prodrug for prostate cancer treatment and to overcome docetaxel resistance.